Surface Plasmonic‐Assisted Photocatalysis and Optoelectronic Devices with Noble Metal Nanocrystals: Design, Synthesis, and Applications. (1st December 2019) - Zada, Amir; Muhammad, Pir; Ahmad, Waqas; Hussain, Zahid; Ali, Sharafat; Khan, Maaz; Khan, Qasim; Maqbool, Muhammad
Abstract: The surface plasmon resonance (SPR) of noble metals is known to improve the efficiency of various processes and devices. The photocatalytic process is the production of fuels and storage of solar photons in chemical bonds without imposing harmful threats to the environment. Photovoltaics are other devices utilizing solar energy for electrical energy. Similarly, other optoelectronic devices like photodetectors absorb photons and convert it into charges via electron–hole dissociation processes. In contrast, light‐emitting optoelectronic devices work based on the phenomenon of charge recombination to produce light. All these devices, however, have efficiency limitations, which impede the application of novel functional materials in these devices. A more direct approach is the utilization of noble metals and their complexes, which significantly enhance the efficiencies of these devices by SPR. This article highlights recent works and applications of noble metals by SPR‐enhanced photocatalysis for hydrogen evolution from water, CO2 conversion into useful compounds, and oxidation of hazardous pollutants. In addition, the plasmon‐enhancement of optoelectronic devices is summarized. Several possible mechanisms that have been previously reported in the literature are discussed in this work, with particular emphasis on different features of these mechanisms involving devices that are not highlighted and therefore need more attention. Abstract : Recently, plenty of noble metal nanocrystals combined with semiconductors/metalloid materials have been developed that can produce strong surface plasmon resonance (SPR) properties. Herein, the latest progress in the design, synthesis, and features of SPR‐assisted photocatalysis, and optoelectronic devices are summarized. Their structure‐related properties and applications in water splitting, green energy storage, and fuel cells are also discussed in detail.